Copyright policies and workflows in libraries a concise handbook - Mower, Allyson (Rowman & Littlefield Publishing Group, 2020)
"Copyright policies take the guess work out of daily library practices such as interlibrary loan, digitization, 3D printing, and using other people's works to advertise library events. Use this book to get guidance on how to create copyright policies and workflows for your library. The book includes sample policies from all types of libraries: academic, public, government, and private"--